Computational simulation of radially asymmetric hydraulic jumps and jump–jump interactions. (15th July 2018) - Singh, Digvijay; Das, Arup Kumar
Highlights: Establish azimuthally asymmetric jump–jump interaction due to impingement jets. Study of flow physics revealing wall adhered jet and back flow in the jump region. Fluidic physics like fountain formation and bent upwash have been modelled. Jets having higher momentum ratio, complete engulfs one jump into another. Abstract: Circular hydraulic jump (CHJ) and its deviation from the azimuthal symmetry due to non-orthogonal impingement of liquid jet on a solid surface are studied using finite volume based numerical framework. Asymmetric interfacial jump has been modelled from volume of fluid (VOF) prediction for a different angle of inclination of a jet from normal of the surface. The extent of asymmetry is found to be increasing as the jet becomes more and more horizontal, deviation from orthogonal impingement. To understand the role of wall adhered jet on jump, flow physics has been studied which reveals back flow in the jump region causing circulation. Moreover, equipotential and heterogeneous jump–jump interactions are studied to predict fluidic features like fountain formation and upwash. Numerical simulations reveal that strength of interacting wall jets play a major role in the formation of a pattern as consequence of neighbouring twin jet impingement. A vertical flat liquid protrusion is observed at equidistant stagnation line from the impingement points of equipotential jets. On the other hand, a curvilinear upwash film has been found out as characteristics of the interaction between heterogeneous strengths of interacting jets. At a higher ratio of jet strengths, complete engulfment of a smaller hydraulic jump as an eye of larger one has been obtained from careful numerical simulation. Physical insights of these rich fluidic phenomena are described using well-resolved velocity vectors in the wall jet and upwash.